Possibilities of application a fixed combination of alogliptin and pioglitazone for type 2 diabetes mellitus treatment - M. V. Shestakova; M. B. Antsiferov; A. S. Ametov; G. R. Galstyan; T. Y. Demidova; A. M. Mkrtumyan; N. A. Petunina (Сахарный диабет)
Hyperglycemia in T2DM is based on three main mechanisms: insulin resistance, progressive β-cell dysfunction, and excess glucose production by the liver.The onset of T2DM is usually preceded by a long period of insulin resistance. Prescribing sugar drugs that affect different links of pathogenesis, reducing a steady decrease in glycemia. To date, in clinical practice, various combinations of hypoglycemic drugs are used, the choice of which is determined by the characteristics of the course of diabetes in the patient, the presence of concomitant diseases and complications of diabetes, as well as the dominant clinical problem. This resolution provides an expert council opinion on the feasibility of using a combination of alogliptin and pioglitazone in patients with type 2 diabetes.